A Consumer Search Behavior Model in the Online Space for Experience-based and Search-based Products - Hashem Aghazadeh; Sajad Khani Pordanjani; Mozhde Khoshnevis (‫مدیریت بازرگانی)
Objective In recent years, e-commerce has experienced significant growth. Although the Internet is an important source of information for both search and experiential goods, the type of information that consumers seek and how they make decisions about these two types of goods are different. Therefore, paying attention to such behavioral differences of consumers has important implications for marketing actions. In today's world, understanding consumers' search behavior for different products is critical to comprehending their purchasing behavior and planning marketing communications. Since little research has been done on consumers' search behavior considering the difference between the types of goods, it is necessary to explore this area more thoroughly. Therefore, the current research aims to provide a model for consumers' search behavior regarding search and experiential goods.